2015
DOI: 10.1002/oti.1396
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Interventions in Chronic Pain – A Systematic Review

Abstract: The use of interventions based on the best available evidence in occupational therapy is essential, and evaluation of research is part of an evidence-based practice. The aim of this study was to assess the quality of studies describing and evaluating the effects of occupational therapy interventions on chronic pain. A systematic review of studies with diverse designs was carried out. A quality assessment was conducted, and the level of evidence was defined using the Research Pyramid Model. Of 19 included studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…More recently, Hesselstrand et al [ 23 ] published a systematic review that assessed the quality of studies describing and evaluating the effects of OT intervention in adults experiencing CP. The main clinical recommendations arising from this review were that (i) OT interventions should start from the identified needs of the client with CP, (ii) no support exists for the effectiveness of electromyographic biofeedback training as a supplement, and (iii) efficacy of instructions on body mechanics was significant during work-hardening treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Hesselstrand et al [ 23 ] published a systematic review that assessed the quality of studies describing and evaluating the effects of OT intervention in adults experiencing CP. The main clinical recommendations arising from this review were that (i) OT interventions should start from the identified needs of the client with CP, (ii) no support exists for the effectiveness of electromyographic biofeedback training as a supplement, and (iii) efficacy of instructions on body mechanics was significant during work-hardening treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, besides Hesselstrand et al [ 23 ], no recent comprehensive review of OT practice in CP management is published. The purpose of the present review was to provide an overview of the current state of knowledge about the OT roles, models, assessments, and interventions methods used with adults living with CP.…”
Section: Introductionmentioning
confidence: 99%
“…(12-14) There is also moderate evidence that OT can improve traumatic brain injury rehabilitation and chronic pain management. (15-17) …”
Section: Introductionmentioning
confidence: 99%
“…Decades of evidence have revealed occupational therapy's toolkit for pain management. From guided imagery and gentle exercise, to relaxation techniques in the form of self-hypnosis, meditation, and yoga, occupational therapists working in pain management settings have used variety of traditional treatment methods to help assist their patients in reducing or coping with their pain (Hesselstrand, Samuelsson, & Liedberg, 2015). However, as demonstrated by the findings from this capstone project, it is of utmost importance that occupational therapists continue to keep up with the latest advances in technology available for rehabilitation.…”
Section: Implications For Occupational Therapymentioning
confidence: 99%
“…Years of evidence-based research have suggested that multidisciplinary rehabilitation is the most efficient form of intervention for pain, with occupational therapy particularly effective in treating chronic pain (Hesselstrand, Samuelsson, & Liedberg, 2015). With the use of interventions and training components such as graded and purposeful activity, environmental modifications, therapeutic exercise and psychologically based management strategies, occupational therapy's contribution to pain management is extensive and has been well-documented (Robinson, Kennedy, & Harmon, 2011).…”
Section: Introductionmentioning
confidence: 99%